Community engagement and participation in ecotourism development in Ikogosi Warm Spring and Arinta Waterfall Corridors - Olakunle Muyiwa Orimaye; Samson Oluwagbemiga Ojo (Journal of Rural Tourism, 2026)
Purpose - This study aims to evaluate the level of community engagement and participation in ecotourism development within the Ikogosi Warm Spring and Arinta Waterfall corridors in Ekiti State, Nigeria. It specifically investigates how socio-economic characteristics influence engagement, assesses current participation levels, and examines the functionality of governance structures supporting ecotourism initiatives. Methodology/Design/Approach - A cross-sectional survey involving 324 households was conducted using structured questionnaires and inferential statistical analyses. The data were used to characterize local socio-economic profiles, measure participation intensity, and evaluate governance mechanisms in both ecotourism corridors. Findings - The results reveal that younger and less tenured residents are more inclined to participate in ecotourism activities, while higher education levels and commercial livelihoods in Ikogosi predict stronger involvement. Despite high awareness levels across both sites, Ipole-Iloro demonstrates more consistent participatory practices—such as regular forums, inclusive planning invitations, and enhanced training opportunities. Governance assessments show that Ipole-Iloro maintains more functional and transparent structures, whereas Ikogosi struggles with irregular consultations and perceived non-functionality. The study highlights that awareness alone does not ensure sustained participation or effective governance. Originality/Value - This study contributes empirical evidence on how demographic, economic, and governance factors jointly shape community participation in ecotourism. By comparing two ecotourism sites with similar contexts but differing governance outcomes, it advances understanding of the mechanisms linking local capacity, institutional functionality, and sustainable tourism development in sub-Saharan Africa.